Mapping scientific research on employee motivation - Moudriq, Faiçal Abou; Soudane, Jalila Ait (Edelweiss Applied Science and Technology, 2024)
This article provides a detailed analysis of publications on employee motivation over the last ten years based on data provided by Scopus. The study examines the distribution of publications by author, identifying prominent researchers and significant international collaborations. It also explores the main areas of research in employee motivation, analyzing dominant fields such as organizational psychology and human resource management. At the same time, the article assesses the contribution of different countries and highlights the most prolific regions. Particular attention is paid to funding sources, highlighting significant sponsors such as government institutions and international research agencies. The results show a trend towards increased institutional funding and greater collaboration between researchers. This analysis provides an overview of developments and trends in employee motivation research, offering valuable insights for future work.